Effect of Frugality and Cognition on Forest Health Tourism Intention–A Mediating Effect Analysis Based on Multigroup Comparison - Li, Ying; Han, Qiang; Wen, Ting (Frontiers in Psychology, 2022)
At present, the market demand for forest health tourism is weak. The main purpose of this study is to investigate whether frugality inhibits the intention of forest health tourism and whether the positive effect of cognition on the intention of forest health tourism can compensate for the inhibition of frugality. Based on mental account theory and planned behaviour theory, this paper constructs a structural equation model with intermediary variables—health consumption mental account and forest health consumption attitude. According to the results of the path analysis of the data, which was collected through the questionnaire survey of urban residents, the positive influence of cognition can compensate for the inhibitory effect of frugality. On this basis, mediating effect analysis based on multigroup comparison is further carried out. This study verifies for the first time the inhibitory effect of frugality on the intention for forest health tourism, enriches the theoretical system of tourism consumer behaviour, and provides a scientific basis for the market positioning of forest health and the formulation of marketing strategies.